Cytotoxic Effect, Antibacterial Activity, and in Silico Evaluation of Berberine Compound from Methanolic Extract of Arcangelisia flava Merr Stems - Sami, Fitriyanti Jumaetri; Nur, Syamsu (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2024)
The Menispermaceae family has 72 genera and more than 400 species, geographically distributed in Asia, Africa, America, and Oceania. The plants of this family are known to have high alkaloid content. One genus of this family is Arcangelisia, with only one species known as Arcangelisia flava Merr. This plant is used as traditional medicine for ailments such as diarrhea, jaundice, and malaria. Therefore, this study was to isolate the alkaloid compounds and test the antibacterial activity against Escherichia coli and Staphylococcus aureus, as well as their toxicity to the shrimp larvae. The isolated compound was confirmed for in silico activity against the target proteins 1UAG (E. coli) and 7RM7 (S. aureus). Based on the analysis of spectroscopic data, UV VIS, FT IR, and NMR, one alkaloid compound was successfully isolated and determined to be a berberine compound. Methanol extract and berberine test against Artemia salina shrimp larvae exhibit active toxicities with LC50 values of 89.13 µg/mL and 75.86 µg/mL, respectively. Antibacterial test result shows that methanol extract and berberine are more active against E. coli than S. aureus. The in-silico activity of the berberine compound supports the result of in vitro antibacterial evaluation. A. flava plant extract has biological capabilities as an anti-microbial and cytotoxic effect, so further development can be carried out in utilizing A. flava plant extract as an effective natural medicine candidate.